Appropriate in vivo follow-up assays to an in vitro bacterial reverse mutation (Ames) test positive investigational drug candidate (active pharmaceutical ingredient), drug-related metabolite, or drug-related impurity - Robison, Timothy W.; Heflich, Robert H.; Manjanatha, Mugimane G.; Elespuru, Rosalie; Atrakchi, Aisar; Mei, Nan; Ding, Wei (Mutation research. Genetic toxicology and environmental mutagenesis, 2021)
Kirkland et al. [Mutation Research/Genetic Toxicology and Environmental Mutagenesis 847 (2019) 403035, https://doi.org/10.1016/j.mrgentox.2019.03.008; Mutation Research/Genetic Toxicology and Environmental Mutagenesis 839 (2019): 21–35, https://doi.org/10.1016/j.mrgentox.2019.01.007] made recommendations on the use of the in vivo comet and transgenic rodent (TGR) gene mutation assays to screen for in vivo mutagenicity. Although it is not directly stated in either of these publications, we are concerned that the reports could potentially be used to support assertions that it is equally acceptable to follow up a positive bacterial reverse mutation (Ames) finding for an investigational drug with either the in vivo TGR mutation assay or an in vivo comet assay. For regulatory genotoxicity assessment, the in vivo follow-up for an in vitro bacterial mutation-positive drug, drug-related metabolite, or impurity should be based upon evaluating a similar endpoint (i.e., mutagenicity) as the intent is to determine if the findings of in vitro gene mutation correlate with findings of in vivo gene mutation (i.e., biologically relevant to the in vitro results). Thus, the most scientifically appropriate in vivo assays would be the TGR mutation assay or, in some circumstances, the in vivo Pig-a assay. An in vivo rodent comet assay or combination of the in vivo micronucleus and in vivo rodent comet assays would generally not be an appropriate follow-up test.